2012
DOI: 10.9753/icce.v33.management.34
|View full text |Cite
|
Sign up to set email alerts
|

Dredging Optimization of an Inlet System for Adjacent Shore Protection Projects Using CMS and Gencade

Abstract: St. Johns County encompasses a 24-km beach and inlet system located in northeast Florida (United States) that includes several interconnected Federal Navigation and Shore Protection Projects that must be managed within a regional context to reduce cost, share sediment, and optimize the volume of sand within the littoral system. The objective of this study is to investigate optimal dredging volumes and intervals, and to determine the beach placement volume and renourishment interval to maintain two Shore Protec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…Further, Garel et al (2014) discussed the limited benefits of dredging the "collapsing ebb-tidal delta" as that reduced the capacity of the existing downdrift shoals to protect the shoreline from wave energy. Beck and Legault (2012) found a similar result in numerical simulations of increased mining footprint and overall sediment volume for adjacent shoreprotection projects. Garel et al (2014) reasoned that the detriments to shoreline erosion outweighed the short-lived benefit of utilizing the readily available sediment and therefore suggested implementing engineered bypassing procedures with respects to a system-wide understanding of sediment dynamics of the area.…”
Section: Tidal Inlet Delta Miningsupporting
confidence: 67%
See 1 more Smart Citation
“…Further, Garel et al (2014) discussed the limited benefits of dredging the "collapsing ebb-tidal delta" as that reduced the capacity of the existing downdrift shoals to protect the shoreline from wave energy. Beck and Legault (2012) found a similar result in numerical simulations of increased mining footprint and overall sediment volume for adjacent shoreprotection projects. Garel et al (2014) reasoned that the detriments to shoreline erosion outweighed the short-lived benefit of utilizing the readily available sediment and therefore suggested implementing engineered bypassing procedures with respects to a system-wide understanding of sediment dynamics of the area.…”
Section: Tidal Inlet Delta Miningsupporting
confidence: 67%
“…Engineering of the inlets through hard structures and soft engineering practices, such as dredging and beach/nearshore placement, is a common approach to mitigate against coastal erosion (Bruun and Gerritsen 2005;Dean 1988Dean 1993Dean and Work 1993). There have been extensive studies conducted on quantifying the total volumes of littoral sediment contained within tidal inlet systems and their application in sediment-based reconstruction and nourishment practice (Beck and Legault 2012;Bruun and Gerritsen 2005;Douglas et al 2003;Finkl et al 2006;Fontolan et al 2007;Houston 2017;Houston and Dean 2016;Oost et al 2014;Schrader et al 2016).…”
Section: Sediment Management At Tidal Inletsmentioning
confidence: 99%
“…An analytical model may use estimated rates of net longshore sediment transport, regional beach erosion rates, and growth rates of ebb/flood-tidal deltas about an equilibrium value to evaluate a long-term exchange between beaches and inlets (Rosati and Kraus, 2009). Beck and Legault (2012) and Legault et al (2012) offer a technical approach at a project scale, which evaluated an optimal volume of mined inlet shoal sediment that could be used to supply adjacent beach nourishment projects without adversely affecting (a) long-term shoal evolution, (b) wave field on adjacent beaches, and (c) inlet navigability. A similar study by Walton and Dean (2011), evaluated maintenancedredging scheduling of the same inlet through an analytical solution of the Pelnard-Considere equation applied to measured shoreline change rates.…”
Section: Engineering Activities At a Barrier-inlet Systemmentioning
confidence: 99%
“…A similar study by Walton and Dean (2011), evaluated maintenancedredging scheduling of the same inlet through an analytical solution of the Pelnard-Considere equation applied to measured shoreline change rates. The analysis by Walton and Dean (2011) suggested that shorter interval dredging and placement of smaller volumes was an optimal approach to avoid detrimental effects to the adjacent beaches, whereas Beck and Legault (2012) emphasized the longest ebb-tidal delta dredging cycle optimized by the volumetric limit that would not result in collapse of the functional sediment bypassing pathways of the tidal inlet.…”
Section: Engineering Activities At a Barrier-inlet Systemmentioning
confidence: 99%
See 1 more Smart Citation